Air Limbah Budidaya Lele dengan Total Dissolved Solid (TDS) berbeda untuk Media Budidaya Daphnia sp - Baruna Kusuma; Rima Oktavia Kusuma; Joni Johanda Putra; Ren Fitriadi (Jurusan Ilmu Kelautan dan Perikanan Politeknik Negeri Pontianak, 2020)
Catfish farming waste contains a lot of organic materials which also contain phytoplankton. One of the organic materials is in the form of dissolved solids / Total Dissolved Solid (TDS). The content of TDS and Phytoplankton can be used as an alternative growth medium for Daphnia sp. Daphnia sp. is a type of cladocera for fish natural food. Catfish culture waste produces different TDS values ​​depending on the cultivation method and the food given to catfish. This study tested catfish culture waste containing different TDS for Daphnia sp. Treatment Media of catfish culture wastewater with 4 treatments of TDS value of 33, 66, 84 and 110 ppm with 3 replications. Daphnia with a density of 20 individuals / L was reared in an aquarium size 60x30x35 cm filled with 50 L of well water with a TDS content of 100 ppm. Treatment of feeding catfish culture wastewater at a dose of 0.5 L per day. Daphnia sp. and 3.5 L of sifon once a week. Water quality tests (DO, pH, temperature, TDS) were carried out every day as secondary data. The results of the analysis of the growth statistical test of Daphnia sp. showed no significant difference. This means that aquaculture wastewater with TDS values ​​of 33 ppm, 66 ppm, 84 ppm, and 110 ppm results in the growth of Daphnia sp. which is just as good. This is because the phytoplankton that grow in wastewater with TDS values ​​of 33, 66, 84, 110 ppm can meet the feed needs of Daphnia sp. during cultivation. From the results of the water quality test the DO and pH values ​​during the study were in good standard conditions for cultivation. The TDS that was observed every day for one week increased this was due to the dissolved solids content of Daphnia sp. The temperature observed during the study fluctuated very large, where at night the temperature was 20 0C while during the day it was 27.5 0C. This drastic temperature fluctuation led to the proliferation of Daphnia sp. not maximal.